Оцінка ризиків та небезпек при роботі з небезпечними відходами - Твердохлєбова, Наталя Євгеніївна; Євтушенко, Наталія Сергіївна (Яроче́нко Я. В., 2025)
Hazardous waste poses significant risks to the environment and human health, and contributes to the degradation of ecosystems through water, soil, and air pollution. Particular attention should be paid to the safety of workers who handle heavy metals and solvents, as well as communities living near waste disposal sites. Improper waste disposal and inadequate infrastructure pose serious risks to the environment and human health. Effective risk assessment, strict safety measures and proper waste management are crucial to minimize hazards and promote sustainable development
Keywords: небезпечні відходи; довкілля; утилізація; професійна безпека; ризики